2020
DOI: 10.1017/s0031182020001560
|View full text |Cite
|
Sign up to set email alerts
|

First report ofOnchocerca lupifrom Israel and confirmation of two genotypes circulating among canine, feline and human hosts

Abstract: Onchocerca lupi is a parasitic filarioid and the causative agent of canine ocular onchocercosis, a zoonotic disease of domestic dogs with sporadic reports in humans. A 13-year-old dog with no travel history outside of Israel was presented to an ophthalmology veterinary clinic in Israel with severe right ocular and periocular disease. After surgical exploration, thin helminths were removed from the dorsal sclera of the eye and identified as Onchocerca lupi by polymerase chain reaction according to the cytochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…However, due to the shortness of the 12S rRNA (298 bp) and nad5 (393 bp) they used, only the cox1 delimitation is discussed here. As an example, O. lupi reported as genotype 1 47 was herein found to encompass four groups of haplotypes: (i) sequences from USA, Hungary, Israel, Greece and Germany, (haplotype 1), (ii) sequences from Portugal (haplotype 2), (iii) sequences from Spain (haplotype 3) and (iv) sequences from Turkey (haplotype 6). In addition, to the different methods used to delineate the phyletic diversity and the difference in the size of the analysed sequences (570 bp versus 652 bp in the present study), the sequence dataset of Rojas et al lacks sequences from the other haplotypes delineated here, such as sequence from Germany (GenBank accession number: KP347443, haplotype 7), Portugal (GenBank accession number: GU365879, haplotype 4) and Iran (GenBank accession number: JN863696, haplotype 5), which explains the differences in haplotype delimitation.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, due to the shortness of the 12S rRNA (298 bp) and nad5 (393 bp) they used, only the cox1 delimitation is discussed here. As an example, O. lupi reported as genotype 1 47 was herein found to encompass four groups of haplotypes: (i) sequences from USA, Hungary, Israel, Greece and Germany, (haplotype 1), (ii) sequences from Portugal (haplotype 2), (iii) sequences from Spain (haplotype 3) and (iv) sequences from Turkey (haplotype 6). In addition, to the different methods used to delineate the phyletic diversity and the difference in the size of the analysed sequences (570 bp versus 652 bp in the present study), the sequence dataset of Rojas et al lacks sequences from the other haplotypes delineated here, such as sequence from Germany (GenBank accession number: KP347443, haplotype 7), Portugal (GenBank accession number: GU365879, haplotype 4) and Iran (GenBank accession number: JN863696, haplotype 5), which explains the differences in haplotype delimitation.…”
Section: Discussionmentioning
confidence: 76%
“…A remarkable diversity with seven genotypes was recorded among sequences from the neglected zoonotic O. lupi . The number of haplotypes of O. lupi was previously investigated by Rojas et al using three mitochondrial markers ( cox1 , 12S rRNA and NADH-ubiquinone oxidoreductase chain 5 ( nad5 )) and two phylogenetic methods (e. g., ML phylogeny and haplotype network) 47 . Rojas et al reported two well-separated genotypes, one with worms from the Old and New Worlds and one from Portugal and Spain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptic and genotypic divergence may lead to differences in pathogenicity, as observed in the canid nematode Onchocerca lupi 27 . In the present study a severe tissue in ammation was induced by infection with P. elegans in squirrel monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Other arthropods have also been considered, but evidence of competent transmission is still missing [ 10 12 ]. This parasite has been documented in Europe, America, Africa, and Asia [ 1 , 13 15 ]. In Europe, the Iberian Peninsula and Greece are known to be endemic areas, but cases have also been reported from Romania, Hungary, and Germany [ 8 , 16 19 ].…”
Section: Introductionmentioning
confidence: 99%